RE-EVALUATION OF CREDITOR PROTECTION IN MORTGAGE ENFORCEMENT: THE LEGAL PERSPECTIVES OF THE AUCTION ENFORCEMENT OF MORTGAGE OBJECTS UNDER THE INDONESIAN LAW - Ayup Suran Ningsih; Norhaini Binti Nion; Paramita Prananingtyas; Harumsari Puspa Wardhani (Faculty of Law, Universitas Diponegoro, 2025)
This paper discusses the usage and application of mortgage rights in Indonesia, especially Law No. 4 of 1996, which is intended to offer legal protection to the creditors and debtors in credit agreements. The collateralized debt agreements are frequently used in business financing, and land is usually the security since it is not prone to fluctuations. With the introduction of the Mortgage Rights Act, a more established framework of such agreements has been made, and legal certainty of creditors has been increased through giving them the power to make claims against collateral in the event of default of the debtor. Nevertheless, the application of mortgage rights, especially in the implementation process, is not without problems, though it has its benefits. Creditors can also challenge laws: a third party can claim them, or a debtor can challenge their efforts, and legal challenges by creditors are not always straightforward to execute due to procedural hold-ups. The law offers preventative legal security in the form of clear agreements and valid collateral instruments. Yet, it is full of repressive provisions, given that creditors are also granted legal action in the event of default. The paper puts a lot of emphasis on the need to balance the interests of the creditors and the interests of the debtors and emphasizes the necessity of having a lean and efficient process. Although the decision of the creditors to buy the mortgage rights presents substantial benefits, the mechanism of overcoming the process of the auction and the ability to guarantee the best outcomes to all participants can be improved. In general, the paper highlights the necessity to develop such legal frameworks further in order to make the goals of the Mortgage Rights Act to the fullest extent, to provide a more stable and reliable financial environment.